RELATIONSHIP BETWEEN QUALITY MANAGEMENT PRACTICES, SUSTAINABLE PRODUCT DEVELOPMENT AND ORGANIZATIONAL PERFORMANCE - Zein Yusoff, Rushaimi; Ahmad, Mohd Akhir (International Business Education Journal, 2013)
This paper presents a study on the relationship between quality management practices and organizational performance, while exploring the influence of sustainable product development in the Malaysian automotive industry context. The demand for high quality is emerging as the single most critical factor for organizations to survive in the ever-expanding global marketplace, where quality is vital in determining the economic success of manufacturing firms. Furthermore, organizations that minimize the negative environmental impact of their product, process recycling of post-customer waste, and establish environmental management system, are poised to expand their market or displace competitors that fail to promote strong environmental performance. A number of empirical studies had also concluded that adopting environmental management does bring certain advantages for the business. However, in the Malaysian automotive industry context, there is still lack of researchers that seek to determine the relationship of quality management practices, sustainable product development, and organizational performance. Even though the relationship between quality management practices and organizational performance has been widely discussed, there still exists potential empirical study on sustainable product development. This paper describes the relationship of sustainable product development as a moderator that influences the relationship between quality management practices and organizational performance. The outcome of this research effort may offer more viable solutions for those firms in the automotive industry to enhance organizational performance in terms of overcoming global competition.